Trusts and patrimonies - Valsan, Remus (Edinburgh : Edinburgh University Press, 2017)
This work explores how the private law concepts of trust and patrimony interact in various jurisdictions, with a view to advancing the understanding of the trust as a fundamental legal concept. It comprises new and previously published papers written by distinguished comparative law scholars. Focusing on the private law of England, Scotland, France, Quebec and the Netherlands, this book investigates whether the common law trust could be understood as a civil law patrimony by appropriation, and whether civil law and mixed traditions could create local versions of the common law trust using patrimony as the main conceptual building block.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 16, 2017).
Keywords: Trusts and trustees; Civil law; Law; Laws of specific jurisdictions & specific areas of law